2024
DOI: 10.3389/fpubh.2023.1252977
|View full text |Cite
|
Sign up to set email alerts
|

Academic medical centres in the Netherlands: muddling through or radical change?

Ester M. M. Cardinaal,
Martijn J. H. Tjan,
Patrick P. T. Jeurissen
et al.

Abstract: IntroductionAcademic medical centres (AMCs) are designed to perform multiple tasks within a single organisation. This institutional complexity gives rise to intricate governance challenges and promotes incrementalism and muddling.MethodIn this study, we hypothesised that radical change could provide a solution to the current incrementalism and we explored the conditions under which such changes could or could not be achieved.ResultsWe conducted unstructured interviews with various high-level stakeholders and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Finally, a European comparison of AMC governance has shown that AMCs struggle to adapt to changing circumstances [2]. A Dutch study found that this is (partly) due to the fact that working with (in) these large organisations is severely hampered by organisational complexity, lack of mutual trust and common interests, and perverse systemic incentives [34]. As noted in the study by van den Hoed et al there are preconditions for the successful implementation of innovative business models [33].…”
Section: Barriers and Challengesmentioning
confidence: 99%
“…Finally, a European comparison of AMC governance has shown that AMCs struggle to adapt to changing circumstances [2]. A Dutch study found that this is (partly) due to the fact that working with (in) these large organisations is severely hampered by organisational complexity, lack of mutual trust and common interests, and perverse systemic incentives [34]. As noted in the study by van den Hoed et al there are preconditions for the successful implementation of innovative business models [33].…”
Section: Barriers and Challengesmentioning
confidence: 99%